2022
DOI: 10.1177/03611981221076449
|View full text |Cite
|
Sign up to set email alerts
|

Decade of Research in Review at the Auburn University Stormwater Research Facility

Abstract: Sediment remains one of the most commonly occurring pollutants affecting the U.S.’s water bodies, as identified by the United States Environmental Protection Agency (USEPA) ( 1). Construction activities largely accelerate soil erosion and subsequent sediment deposition. The National Pollutant Discharge Elimination System Construction General Permit requires construction operators to implement erosion and sediment control (E&SC) plans to minimize downstream implications from sediment-laden discharge. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…The low awareness and level of soil conservation management is the biggest risk source of soil loss in CSM, which is consistent with the research results of Houser [21]. In addition, this is also supported by another perspective, propounding that it is necessary for Auburn University [22] to train construction personnel in soil conservation. The construction unit should follow the rules and regulations, and implement the soil conservation measures for the construction site.…”
Section: Analysis Of the Weight Of Influencing Factorssupporting
confidence: 84%
See 2 more Smart Citations
“…The low awareness and level of soil conservation management is the biggest risk source of soil loss in CSM, which is consistent with the research results of Houser [21]. In addition, this is also supported by another perspective, propounding that it is necessary for Auburn University [22] to train construction personnel in soil conservation. The construction unit should follow the rules and regulations, and implement the soil conservation measures for the construction site.…”
Section: Analysis Of the Weight Of Influencing Factorssupporting
confidence: 84%
“…The difference in the management level will affect the effect of soil conservation measures. Improving the management awareness of soil conservation for construction project management per-sonnel can play a considerable role in controlling soil erosion in construction projects [22]. According to the identity of the main management personnel in the CSM, the management measures are divided into three factors: construction unit management (CU), supervision unit management (SU) and government management (GM).…”
Section: Management Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the guidelines used by several states in sediment barrier design, a maximum drainage area of 0.5 acres (0.20 ha) per 100 linear ft (31 m), an unprotected upstream drainage area of 218 ft (66 m) in length, which is the length of a 0.5 acre (0.20 ha) area with a width of 100 ft (30 m), was used and kept constant through all modeling ( 30 ). This representative drainage area was also used in large-scale laboratory testing at the Auburn University Stormwater Research Facility and allows modeling results to be compared with past sediment barrier testing results ( 31 , 32 ). The length of the vegetated buffer was kept constant at 50 ft (15 m) to investigate and generate data on how much sediment was removed by a 50-ft (15-m) vegetated buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have been investigating the use of flocculants in construction stormwater treatment for filling the existing gap in knowledge through laboratory and field testing. For instance, the use of flocculants in sediment basin applications was investigated in several studies and showed substantial turbidity reduction in construction stormwater runoff ( 1719 , 37 , 38 ). Wood et al ( 39 ) evaluated the feasibility of stormwater treatment by conventional and lamellar settling with and without flocculant injection and obtained up to 83% TSS removal with flocculant usage.…”
Section: Introductionmentioning
confidence: 99%